Agility And Some Forms of Flexibility and Their Relationship to the Accuracy of the Smash Hit to Different Areas in Volleyball for Players of Al-Hadara University College Private, Aged 18-22 - Abdul-Razzaq Abdullah Ibrahim (Penerbit Jurnal Indonesia, 2025)
This study aims to examine the relationship between selected forms of flexibility and agility with the accuracy of spike execution in volleyball players aged 18–22. The research focuses on identifying which physical components most significantly influence spike accuracy in both straight and diagonal directions. A descriptive correlational research design was employed. The research sample consisted of 25 male volleyball players from Imam University College, selected randomly from the total population after excluding libero and injured players. Data were collected using standardized physical tests, including spinal flexibility tests, shoulder joint range of motion tests, Barrow agility test, and spike accuracy tests targeting specific court areas. Pearson’s correlation coefficient was used to analyze the relationship between flexibility, agility, and spike accuracy. The results revealed a significant correlation between spinal extension flexibility and straight spike accuracy, as well as between dynamic spinal rotation and spike accuracy in both straight and diagonal directions. Agility showed a significant relationship with straight spike accuracy but not with diagonal spike accuracy. Conversely, shoulder joint flexibility demonstrated no significant correlation with spike accuracy in either direction. These findings indicate that spinal flexibility and agility play a more critical role than shoulder flexibility in enhancing spike accuracy. The study concludes that volleyball training programs should prioritize dynamic spinal flexibility and agility development to improve offensive performance.